From the Port City of Beirut to Beirut Central District - Roula El Khoury; Paola Ardizzola (Spool, 2022)
The repeated destructions and reconstructions of Beirut have been widely acknowledged and conveyed from one generation to the next through different narratives, anecdotes, literature, and popular cultural productions. This paper describes the historical transformations of the city of Beirut from an old harbour city to a generic central district through a selection of dominant narratives, as well as alternative counter-narratives and anecdotes.